2013
DOI: 10.1186/1475-2867-13-59
|View full text |Cite
|
Sign up to set email alerts
|

Role of relaxin-2 in human primary osteosarcoma

Abstract: BackgroundThe aim of this study was to clarify the clinicopathological outcome of serum relaxin-2 and tissues relaxin-2 expression levels in human primary osteosarcoma (OS), and to explore the roles of relaxin-2 inhibition and determine its possibility as a therapeutic target in human osteosarcoma.MethodsReal-time quantitative RT-PCR assay was performed to detect the expression of relaxin-2 mRNA in 36 cases of human osteosarcoma tissue samples. Serum relaxin-2 levels was measured in ELISA-based method in the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…To date, H2 relaxin has been implicated in the progression and invasiveness of a variety of cancers, including breast, thyroid and ovarian/endometrial cancers . Some recent preliminary evidence suggests a role for relaxin in the cancers of the liver, bone, uterus and esophagus . One study showed that H2 relaxin transcript expression was present in all neoplastic breast tissues compared with only 3 out of 8 normal tissues .…”
Section: Other Reproductive Tissue‐based Cancersmentioning
confidence: 99%
“…To date, H2 relaxin has been implicated in the progression and invasiveness of a variety of cancers, including breast, thyroid and ovarian/endometrial cancers . Some recent preliminary evidence suggests a role for relaxin in the cancers of the liver, bone, uterus and esophagus . One study showed that H2 relaxin transcript expression was present in all neoplastic breast tissues compared with only 3 out of 8 normal tissues .…”
Section: Other Reproductive Tissue‐based Cancersmentioning
confidence: 99%
“…Human soft tissue sarcomas usually develop first in an extra thoracic location but have an increased propensity to metastasize to the lung. It has been noted that extra-thoracic tumors send out pilot cells that could attach to the pulmonary endothelium and could in theory alter regional lung mechanics by either stiffening the lung tissue or by increasing fluid and inflammatory cell accumulation near the pilot cell attachment in the endothelium producing changes in lung compliance [ 1 8 ]. We hypothesized in this study that prior to the computed tomographic-based (CT) visualization of a metastatic lung nodule, CT measures of regional lung mechanics [ 9 21 ] could detect changes in lung compliance not visible to the human eye on standard chest CT examinations and that these changes in compliance would precede the development of metastatic lung nodules that are subsequently visible on CT.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling by relaxin-2 through its target receptors enhances the growth of pubic ligaments and ripening of the cervix during birth. Several groups, including ours, have demonstrated that H2 relaxin plays a role in OS carcinogenesis [ 3 ]. However, the mechanism that RLN2 functions in detail is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been found that chemically synthesized AT-001, an analog of human RLN2, could suppress PC3 xenograft growth and sensitize PC3 xenografts to docetaxel, standard first-line chemotherapy for HRPC [ 28 ]. We have previously found the levels of RLN2 mRNA expression in OS tissue samples were significantly higher than those in the corresponding nontumor tissue samples [ 3 ]. Whether RLN2 could be important therapeutic targets for overcoming chemoresistance or whether RLN2 overcomes chemoresistance by AKT/NF- κ B pathway is not very clear to date.…”
Section: Introductionmentioning
confidence: 99%